2020
DOI: 10.1007/s41042-020-00035-7
|View full text |Cite
|
Sign up to set email alerts
|

Do-it-Yourself Activities and Subjective Well-Being

Abstract: We examined predictors of subjective well-being (SWB) associated with do-it-yourself (DIY) activities in a sample of 525 self-identified DIYers through Amazon's Mechanical Turk. We hypothesized that positive mood, feeling energized or aroused, and experiencing flow during DIY activities, would each contribute to subjective wellbeing (SWB), and, that negative self-focus would not. We also controlled for individual differences that could affect the experience of negative self-focus and flow: quiet ego and depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…This measure was completed at T1 only. Student scores on the QES ( M = 5.16, SD = 0.63) were comparable to previously published studies (Collier & Wayment, 2018; Collier et al, 2019).…”
Section: Methodssupporting
confidence: 86%
See 3 more Smart Citations
“…This measure was completed at T1 only. Student scores on the QES ( M = 5.16, SD = 0.63) were comparable to previously published studies (Collier & Wayment, 2018; Collier et al, 2019).…”
Section: Methodssupporting
confidence: 86%
“…Finally, when controlling for the effects of treatments on positive mood, we found there was uniform and strong flow and arousal across all intervention conditions. Previous studies with retrospective and cross-sectional samples of artists (Collier & von Károlyi, 2014), Makers (Collier & Wayment, 2018), and DIYers (Collier et al, 2019) have reported that both arousal and flow were critical for rejuvenation and subjective well-being to occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tasks with optimal levels of challenge and skill level can lead to states of flow where an individual is engaged and absorbed in an activity for its own sake rather than for any extrinsic reason (Csikszentmihalyi, 2008;Csikszentmihalyi & Csikszentmihalyi, 2000). Previous research has found a positive association between flow and both positive affect (Collins et al, 2009) and life satisfaction (Sahoo & Sahu, 2009); and a negative association between flow and negative affect (Collins et al, 2009) and a depressed or anxious mood (Collier et al, 2020). Engaging in flow-inducing activities has been shown to improve positive affect.…”
mentioning
confidence: 99%